Symbolism and Sound: A Semantic Study of Figurative Language in Bruno Mars’ 24K Magic - Nurazizah, Maya Siti; Sakinah, R Myrna Nur; Suswanto, Deni (English Language in Focus (ELIF), 2025)
This study explores the role of figurative language in shaping thematic meanings in Bruno Mars’ 24K Magic album. Using qualitative semantic analysis, it examines how metaphors, similes, hyperboles, personifications, and metonymies enhance the album’s themes of luxury, confidence, romance, and celebration. Analyzing nine tracks, the study identifies 45 instances of figurative language—metaphors (15), similes (10), hyperboles (8), personifications (7), and metonymies (5)—demonstrating how these devices enrich lyrical aesthetics, deepen emotional engagement, and create vivid imagery. Findings highlight the power of figurative language in reinforcing thematic coherence and amplifying listener interpretation. This research contributes to semantic analysis in music by bridging linguistic and literary perspectives, offering insights into how symbolic language enhances meaning.